The Misuses of Reliability Coeffient and Sampling Variance in Educational Research - Dali S. Naga (Universitas Negeri Malang, 2016)
Many educational researchers report the reliability of their data. They also report tha sampling techniques used in their research. Some of the reports treat the reliability coefficients and sampling variances incorrectly. It is a misuse of the reliability coefficients and sampling variances in educational research